2014
DOI: 10.3892/or.2014.3336
|View full text |Cite
|
Sign up to set email alerts
|

PEG-liposomal oxaliplatin combined with nuclear factor-κB inhibitor (PDTC) induces apoptosis in human colorectal cancer cells

Abstract: To achieve sufficient antitumor activity for colorectal carcinoma, optimization of the therapeutic regimen is of great importance. The aim of the present study was to investigate the effects of polyethylene glycol (PEG)-liposomal oxaliplatin (L-OHP) on the induction of apoptosis in human colorectal cancer SW480 cells and how the nuclear factor-κB (NF-κB) pathway may contribute to mediating PEG-liposomal L-OHP-induced apoptosis. PEG-liposomal L-OHP was prepared and used to treat colorectal cancer SW480 cells. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…These results showed that prepared nanoliposomes have acceptable performance, because it is reported that the survival rates of cancer patients was related to the percentage of apoptotic cancer cells as well as higher concentrations of antitumor agents in the location of tumors. [ 28 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that prepared nanoliposomes have acceptable performance, because it is reported that the survival rates of cancer patients was related to the percentage of apoptotic cancer cells as well as higher concentrations of antitumor agents in the location of tumors. [ 28 29 ]…”
Section: Discussionmentioning
confidence: 99%